REKONTEKSTUALISASI HASIL INTEGRASI NILAI BUDAYA DALAM PERENCANAAN KOTA YOGYAKARTA - Dwi Sukma Bayu Wardhana; Petrus Natalivan Indradjati (Diponegoro University, 2019)
In 2015, UNESCO initiated the inclusion of local culture into sustainable urban planning and development. Yogyakarta has a great historical-cultural potential, where the city has been named as a special region established under Undang-Undang No. 13/2012. By referring to the UNESCO initiation and Undang-Undang No. 13/2012, Yogyakarta has the advantage to initiate the local culture into its sustainable urban planning and development. Though culture is intangible; but by taking the law enforcement and its historical-cultural potential into Yogyakarta is now eligible to develop a city planning on a cultural basis. This research is to explore the integration of Yogyakarta culture into city planning based on eight aspects of culture based spatial planning, in relation to planning guidance/regulation, empirical condition and 14 cultural values of Yogyakarta. The research has shown that 14 Yogyakarta cultural values, in accordance with 7 of the 8 principles of culture based spatial planning (except connectivity principle) and 5 out of 14 cultural values of Yogyakarta has cohesive relationship with 8 aspects of culture based spatial planning, but it is not manifested on the current planning and implementation. This research reinforces that socio-cultural basis of planning relief on three variables respectively cultural aspect, human resources, and nevertheless the cultural awareness